The relationship between sleep pattern and depression in Chinese shift workers: A mediating role of emotional exhaustion. (29th April 2019) - Hu, Yixin; Niu, Zhaoxiang; Dai, Lejiao; Maguire, Rebecca; Zong, Zhaobiao; Hu, Yu; Wang, Dawei
Abstract: Objectives: To explore the relationship between sleep pattern (morningness–eveningness) and depression in Chinese shift workers ("Three Shifts" workers), and to examine whether emotional exhaustion plays a mediating role in this relationship. Study Design: We examined the impact of sleep pattern on the depression of three shifts workers, focusing on the mediating effect of emotional exhaustion. Methods: A total of 1303 shift workers in the north and south of China were invited to participate in this study using convenience sampling. They completed a questionnaire which collected information on socio‐demographic variables, along with measures of sleep pattern, depression, and emotional exhaustion. Using structural equation modelling, the mediating role of emotional exhaustion in sleep pattern and depression was explored. Results: Of the three shifts workers 46.43% reported symptoms of depression; 27.84% identified as morning types while only 6.56% were evening types, with the remaining 65.60% falling into the intermediate category. There was a negative correlation between sleep pattern and depression, and between sleep pattern and emotional exhaustion, but a positive correlation between emotional exhaustion and depression. As predicted, emotional exhaustion played a mediating role in the relationship between sleep pattern and depression. Conclusions: Having an evening sleep pattern was a risk factor for depression in three shifts workers; however, emotional exhaustion mediated the relationship between sleep pattern and depression. This finding may inform interventions aimed at reducing the level of depression within three shifts staff.